Pendidikan Multikultural Berdasarkan Nilai-Nilai Kristiani (Galatia 5:22-23) Suatu Upaya Penguatan Identitas Bangsa - Menti Riani Lubis; Maria Titik Windarti (Asosiasi Riset Pendidikan Agama dan Filsafat Indonesia, 2024)
Pancasila as the foundation of the Indonesian state has norms that regulate religious and cultural diversity. However, in practice, diversity is still a task that must be taken seriously.” This article discusses problems that arise due to diversity, such as conflicts between religious, ethnic and cultural communities. The purpose of writing this article is to provide relevant views related to multicultural education and its relationship with the principles of Christian values so that a tolerant nation is born. Indonesia is a nation that has different religions, ethnicities and cultures, but these differences often become one of the triggers for conflict. With the application of a strong multicultural understanding in a nation, Indonesia will become a strong nation and accept differences as heritage. The method used in writing this article is descriptive qualitative method, by conducting a literature review from several relevant sources, describing a thing, phenomenon, or social setting in explaining or describing related to the topic of multicultural and Christian values. By instilling multicultural education with the principles of Christian values (Galatians 5:22-23) such as love, peace, joy, kindness, generosity, faithfulness, gentleness, self-control is relevant to create a nation that is tolerant, lives in harmony, accepts and respects each other despite having different backgrounds.